Application of Schmidt's theory in self-regulatory motor learning - Gula-Kubiszewska, G. (Human Movement, 2004)
Purpose Cognitive strategies stand for "inner behaviour (thoughts) and outer behaviour that enable storing and retrieving information from memory." Metacognitive strategies are "procedures used in planning, supervising and regulating activities on the symbolic level, i.e. in the learner's mind." Learning is considered to be an active, aim-oriented process of constructing knowledge in one's own mind. This process involves supervision of learning content, course and effects. Declarative knowledge covers "knowing that" and refers to things, events and relations between them. Procedural knowledge stands for "knowing how" and covers the knowledge of ways of acting. When supervision of strategy application comes from the inside (learners regulate their acting on their own) and not from the teacher, one can refer to the so-called self-regulatory learning. An effective self-regulatory model for learning texts and for motor learning is that of Simons and de Jong. In learning a motor program there are two components: learning general structure of the program and learning how to attain program parameterization. Schmidt believes that the learner forms two representations of abilities. The first is recall memory, which determines the motor program itself (a linked sequence of actions); the second is recognition memory, based on feedback information and external sensory consequences. In the motor learning process attention should be paid to the proper execution of the motor program and appropriate use of this knowledge to improve the program. Correction should be based on relation to recognition memory.